Ethical instrumentation of integrated waste management - Adebayo, Opatokun Suraj; Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir (2010)
waste is as old as man and its culture management change with time according to complexity of its formation. the contemporary increase population, industrial development and various anthropogenic activities necessiatate the need for an integrated Waste Management System (IWMS. This study reviews the technological requirement of waste management by considering the ethical significant of entire stakeholders-the waste generators, the policy makers and the waste managers - to achieve a sustainable waste management system in the society. Thus, emphasizing that integrated Waste Management could be realized by incorporating value based regulations and policies moral rearmament, and intrinsic data mining are vital instrument.